Colour image watermarking based on wavelet and QR decomposition - Rasti, Pejman; Anbarjafari, Gholamreza; Demirel, Hasan (Institute of Electrical and Electronics Engineers Inc., 2017)
In this work, a new image watermarking algorithm on colour images is proposed. The proposed algorithm divides a cover image into three colour bands of red, green and blue. Then the following tasks are done on all three channels separately. First, Each colour band is divided into patches of small sizes then the entropy of each patch is calculated. At this step a threshold is found based on the average entropy of all patches and following is applied to all patches which have entropy lower than the threshold. A wavelet representation of each patch are given by applying a discrete wavelet transform. Then Singular value decomposition, orthogonal-triangular decomposition, and a chirp z-transform are used to embed a watermark on the cover image. Several signal processing attacks are applied on watermarked images in order to robustness of the algorithm. The Proposed algorithm is compared with one conventional and two state-of-the-art algorithms. Experimental results show superiority of the proposed algorithm compare with other algorithm in the area of image watermarking. © 2017 IEEE.
25th Signal Processing and Communications Applications Conference, SIU 2017 -- 2017-05-15 through 2017-05-18 -- Antalya -- 128703
Keywords: CZT; digital Image Watermarking; DWT; Entropy; QR; SVD